Arthroscopic Ischial Tuberoplasty: Treatment of Ischiofemoral Impingement - Lakshmanan Sivasundaram MD; Mario Hevesi MD, PhD; Kyleen Jan BS; Katlynn Paul BS; Shane J. Nho MD, MS (SAGE Publishing, 2022)
Background: Ischiofemoral impingement is a rare but increasingly recognized as a source of hip pain. Its etiology is often multifactorial and can be due to congenital, iatrogenic, or extra-articular pathology. Prior literature has described lesser trochanter osteoplasty and iliopsoas release for the treatment of ischiofemoral impingement, but postoperative hip flexor weakness has been noted with this technique. We present a novel technique for the treatment of ischiofemoral impingement, with resection of the ischial tuberosity. Indications: Patients with ischiofemoral impingement that remain symptomatic despite nonsurgical management, or patients with persistent gait abnormalities, are considered for surgery. Technique Description: In the prone position, direct posterior and posterolateral arthroscopic portals are created in the gluteal fold. The posterior femoral cutaneous and sciatic nerve are identified. Fluoroscopy is used to identify the region of impingement on the ischial tuberosity and the overlying hamstring tendon is elevated off the tuberosity. An arthroscopic burr is used to resect the tuberosity. Fluoroscopy is utilized to confirm adequate resection. This is combined with a dynamic examination under direct arthroscopic visualization with the hip in an extended, adducted, and externally rotated position. To repair the hamstring tendon, 2 double-loaded anchors are placed into the ischium, the sutures of which are used to repair the hamstring tendons using a horizontal mattress configuration. Patients undergo a stepwise postoperative physical therapy protocol, followed by a functional testing profile prior to return to competitive sport. Results: Significant improvements in patient-reported outcomes have been reported following treatment of ischiofemoral impingement, with some studies reporting Hip Outcome Score-Activities of Daily Living (HOS-ADL) >90 at 2 years postoperatively. Athletes have been able to return to sport at a mean 5.6 months after surgery. Large studies have yet to report on outcomes compared with nonsurgical or open techniques. Discussion/Conclusion: Recent advancements in endoscopic techniques have allowed for adequate visualization and release of ischiofemoral impingement. We present our endoscopic technique of ischial tuberoplasty, which, compared to lesser trochanter osteoplasty and iliopsoas release, may reduce the incidence of postoperative hip flexor weakness.